DEVELOPMENT OF AN INTERACTIVE LEARNING MODULE BASED ON THE ADDIE MODEL FOR THE TOPIC OF MECHANICAL PROPERTIES IN STEEL AT VOCATIONAL COLLEGE - Che Mut, Che Mohammad Fattihi Ekhmal; Ismail, Mohd Erfy; Abd. Hamid, Rosmawati; Ishak, Khairul Amin; Mohamad Amin, Ahmad Zaki; Ismail, Irwan Mahazir (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The use of interactive learning modules has the potential to enhance the understanding of mechanical concepts in steel while providing a highly engaging and interactive learning experience for students. However, traditional learning approaches that are less effective make it challenging for students to understand and apply knowledge in practical situations. This study aims to develop an interactive learning module using the FlipHTML5 application, based on suitable learning theories for the Diploma in Welding Technology subject, according to the vocational college syllabus. Additionally, it seeks to assess the impact of FlipHTML5 in improving usability in terms of design, functionality, and content relevance for learning the mechanical properties of steel, while addressing the lack of teaching learning materials (TLM) in the subject of Metallurgy and Corrosion Control. The research methodology involves product development through a quantitative approach. The quantitative research design was employed to ensure systematic data collection and analysis in evaluating the effectiveness of the developed module. In addition, the study instrument uses a questionnaire based on a 5-level Likert scale, namely, strongly disagree, disagree, neutral, agree, and strongly agree. It also follows the product design and development framework using the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model as a guide for developing the interactive learning module. The pilot study involved 30 fourth- and fifth-semester students at Batu Pahat Vocational College, while the main study was conducted on 40 fourth- and fifth-semester students at Muar Vocational College using a simple random sampling method. Data collected were analyzed using descriptive statistics through Statistical Package for the Social Sciences (SPSS) version 30, with a Cronbach’s Alpha value of 0.942 in the pilot study, indicating a high level of instrument reliability. The analysis results reported mean values for usability in terms of design (mean = 4.47), module functionality (mean = 4.36), and content relevance (mean = 4.40). This reflects a positive impact on the use of the interactive learning module for the topic of mechanical properties of steel. The discussion revealed that the interactive learning module developed based on the ADDIE model could enhance students’ understanding. This includes interactive elements such as videos, infographics, and interactive quizzes, helping students grasp complex concepts effectively. In conclusion, this study has a positive impact by providing an innovative learning approach that improves students’ understanding. It also has the potential to serve as a reference model for developing interactive learning materials for technical subjects.